Estrategias didácticas y competencias específicas del programa MVZ UNIPAZ, respecto a resultados de las pruebas Saber Pro (2020)
In 2016, 2017 and 2018, the results of the Saber Pro State Tests yielded data located below the national average, in response to this situation, the Veterinary Medicine and Zootechnics (MVZ) program of the University Institute of La Paz ( UNIPAZ) has been developing improvements in the didactic strategies that favor overcoming this situation, this motivated this study, which set as a general objective to analyze the didactic strategies applied in the Program of Veterinary Medicine and Animal Husbandry of UNIPAZ, facing the demands of competences specific to the professional training of the career. A qualitative and quantitative mixed or complementary study was carried out, which led to the following conclusions: the actors consider that the didactic strategies used in the UNIPAZ MVZ program to achieve the competences are not adequate, the students do not They are prepared to carry out academic work under these strategies and these are not consistent with generic reading and critical thinking skills, written communication, and teamwork, which does not generate a good basis for specific skills; On the part of the teachers, it was evident that they concentrate on their area of knowledge, however, there is not a good development of the specific competences. It is necessary to work on the training of teachers and the monitoring of their pedagogical action.